Online appointment application system - Norlidiyana, Tabroni (2006)
Internet has become one of the largest sources of information worldwide,it facilitates the delivery of educational and training materials that supports education and training process which can be retrieved through the World Wide Web (WWW).Being a centre point for technological development for the past two decades,the Internet's facility for real-time interaction have made computer-based training, or web-based training become more practical for meeting the educational needs.As an aid to the above requirements,this thesis presents the development of On-line Appointment Application System & Notification via SMS for students especially under the Faculty of Computer Systems and Software Engineering to send their application to set an appointment through online and get their approval immediately via short message service (SMS) sending by that lecturer.Therefore,student can get the latest information about the result of the application directly from the system.This project will be divided into two interfaces, namely student and lecturer or staffs interface.